Enhacing Cloud Security: Combining Homomorphic and Elliptic Curve Cryptography for Resilient Fusion - Srinivas, Madhira; Sammulal, Porika (International Journal of Computer Sciences and Engineering, 2022)
This study introduces a unique method for strengthening healthcare data security by combining homomorphic encryption (HE) with elliptic curve cryptography (ECC) in a way that is both robust and effective. Patients' right to privacy and data security must be protected as the cloud computing industry moves towards a model based on data-driven insights. For safe data processing and analytics, we provide a hybrid system that takes advantage of ECC's efficiency in key exchange while also including HE's privacy-preserving characteristics. We illustrate the efficacy of our suggested strategy through a thorough comparative analysis, actual implementation, and case study in a Cloud computing setting. The hybrid architecture prevents sensitive information from falling into the wrong hands and facilitates secure and efficient data flow among legitimate parties. Our results highlight the promise of this robust union to revolutionize cloud securityand execution time,encryption,and decryption time compared to other crypto algorithms, opening doors to betterand more efficient programs for future endeavors.